Effect of family-centered empowerment model on HOPE of adolescents with thalassemia major - Mardhiyah, Ai; Panduragan, Santhna Letchmi; Mediani, Henny Suzana; Yosep, Iyus; Shalahuddin, Iwan; Hafitriany, Syifa Aulia (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
Thalassemia Major is a hereditary blood disorder and is a chronic disease that can cause various problems regarding future expectations for sufferers. Adolescents with thalassemia major experience various psychosocial problems which have an impact on decreasing hope, quality of life, interpersonal relationships, self-esteem which results in depression. The aim of this study was to identify the effect of the family centered empowerment model on the hope of adolescents with thalassemia major in Indonesia. This study uses a quasi-experimental design. The sample in this study were 240 adolescents with thalassemia major. Participants were given 4 sessions of family empowerment interventions for 4 weeks. Each session is carried out for 90 minutes. this study uses Children's Hope Scale (CHS) for data collection. Data analysis used independent t test and chi-square. The results of the study showed that the hope score increased significantly after the family-centered empowerment model in the intervention group (P=0.002). In addition, there was a significant difference between the intervention group and the control group in the mean of hope score among adolescents with thalassemia. The family centered empowerment model is an effective intervention to improve the hope for adolescents with thalassemia.